Selenium and Coenzyme Q10 Supplementation and Sex Differences in Cardiovascular Mortality Results from a Prospective Randomized Double-Blind Placebo-Controlled Trial in Elderly People Low in Selenium - Urban Alehagen; Jan Olav Aaseth; Lutz Schomburg; Trine B. Opstad; Anders Larsson; Jan Alexander (Antioxidants)
Background: Low selenium intake and age-related decline of coenzyme Q10 (CoQ10) have been associated with an increased risk of cardiovascular disease (CVD) and oxidative stress. In a randomised placebo-controlled trial (RTC) in elderly people with low selenium levels, the supplementation with selenium and CoQ10 reduced CVD and mortality. However, whether the supplementation elicited sex-specific benefits remained to be explored. Methods: Elderly Swedish persons (n = 443; balanced sex ratio) receiving selenium yeast (200 µg/day) and CoQ10 (200 mg/day) combined or a placebo for four years were followed for additional six years. The response to supplementation, cardiovascular (CV) mortality, and risk factors were determined at four and ten years. Kaplan–Meier analyses, ANCOVA, repeated measurements of variance, and Cox proportional hazard regression analyses were performed. Results: The measured 10-year CV mortality rate was lower in females, and supplementation reduced this risk to a greater extent compared to in males. The improved survival rate apparently kicked in later in females than in males. At baseline, males had a higher smoking rate, increased inflammation and oxidative stress, and a higher prevalence of more advanced ischaemic heart disease (IHD) and signs of heart failure. When stratified by sex, in individuals with IHD, the intervention improved CV survival in both sexes, whereas supplementation had a more pronounced effect in females without IHD at inclusion. Supplementation diminished inflammation and oxidative stress, impaired the increase of NT-proBNP, and improved renal function in both sexes. Conclusions: The supplementation improved CV survival, especially in women. The higher prevalence of structural CVD and smoking in males may have contributed to the observed greater supplementation benefits in females. The preventive impact of selenium and CoQ10 supplementation in elderly males and females may be particularly strong and meaningful in the early stages of CVD development.